1995
DOI: 10.1172/jci118161
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba histolytica trophozoites induce an inflammatory cytokine response by cultured human cells through the paracrine action of cytolytically released interleukin-1 alpha.

Abstract: Infection with the protozoan parasite Entamoeba histolytica results in a high mortality worldwide. To initiate infection, E. histolytica trophozoites in the bowel lumen penetrate the epithelium, and cause extensive lysis of host cells. The acute amebic lesions in animal models are characterized by infiltration with inflammatory cells, particularly neutrophils. The acute host response is likely important for determining whether the infection will spread systemically, but little is known regarding the signals wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
93
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 60 publications
8
93
0
2
Order By: Relevance
“…histolytica trophozoites induced expression of proinflammatory cytokines such as IL-8, IL-1a/b and GM-CSF from HT-29 human colonic epithelial cells. These results are compatible with the previously published report by Eckmann et al [3]. The cytokines in the present study are proinflammatory, and could recruit inflammatory cells, including PMNs and monocytes.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…histolytica trophozoites induced expression of proinflammatory cytokines such as IL-8, IL-1a/b and GM-CSF from HT-29 human colonic epithelial cells. These results are compatible with the previously published report by Eckmann et al [3]. The cytokines in the present study are proinflammatory, and could recruit inflammatory cells, including PMNs and monocytes.…”
Section: Discussionsupporting
confidence: 94%
“…Eckmann et al [3] have reported narrow dose-response curves for E. histolytica stimulation of IL-8 secretion; this was also the case with IL-8 mRNA expression in this study. As shown in Table 1, increased IL-8 expression occurred in a dose-dependent manner.…”
Section: Il-8 Mrna Expression According To the Ratio Of Number Of Ht-supporting
confidence: 80%
“…Several reports have suggested that proinflammatory cytokines can be released from infected epithelial cells following host cell lysis after infection (27)(28)(29). Chlamydiae replicate in a specialized vacuole in the host cell cytoplasm and induce host cell lysis at the end of its developmental cycle (30).…”
Section: Discussionmentioning
confidence: 99%
“…Little is known of how a microbial pathogen might regulate IL-18 secretion from epithelial cells. IL-1␣ is an upstream cytokine that regulates the de novo production of other proinflammatory cytokines and chemokines, such as IL-8, IL-6, GM-CSF, growth-regulated oncogene-␣, and TNF-␣, from epithelial cells or endothelial cells infected with microbial pathogens such as C. trachomatis (22), Rickettsia conorii (28), Entamoeba histolytica (27), Toxoplasma gondii (29), and respiratory syncytial virus (32). Our observations demonstrate that increased IL-18 secretion in epithelial cells after C. trachomatis infection is not mediated by IL-1␣ or other secreted factor(s), indicating that IL-18 secretion from epithelial cells infected with chlamydia differs from that regulating the secretion of IL-8, IL-6, GM-CSF, TNF-␣, and other proinflammatory cytokines or chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that IECs serve as the effectors of mucosal immune system, responding to pathogens by secretion of proinflammatory mediators and acting as antigen presenting cells (55)(56)(57). Coculture of epithelial cell lines with E. histolytica trophozoites resulted in increased production of TNF-α, IL-1α, IL-6, IL-8, GROa, and GM-CSF by the epithelial cells (57). Similar results were observed in the SCID mousehuman intestinal xenograft (SCID-Hu-INT) model, where E. histolytica infection resulted in elevated production of IL-1β and IL-8 by the human intestinal xenograft (56).…”
Section: Interactions Of Intestinal Epithelial Cells With E Histolyticamentioning
confidence: 99%